Study of the Effectiveness of Statins in Coronary Heart Disease After Stentration in Persons of the Uzbek Population - Norqulov Zokir Urolovich; Ochilov Shohsuvor Zokirovich; Tuychiyev Sardor Azamatovich (Genius Journals, 2022)
Statins occupy the main place in the treatment of ischemic heart disease CHD), in the development of which lipid metabolism disorders and inflammation are important. The effects of atorvastatin and rosuvastatin on the lipid spectrum, inflammatory factors, transaminase activity and total bilirubin content, structural and functional state and intracardiac hemodynamics of the left ventricle of the heart in patients with CHD of the Uzbek population after stenting, taking into account the polymorphism 13 of the ApoE and CYP2C19 * 2 genes, were studied. The favorable effect of statins on the studied parameters and the course of the disease was shown, and the data of genetic studies made it possible to select the most effective and safe doses of drugs. Key words: coronary artery disease, coronary artery steni, atorvastatin, rosuvastatin, lipids,, ApoE and CYP2C19 * 2 polymorphisms.
Keywords: Lipoproteins; Coronary Artery; Lipid-Lowering; Antiatherosclerotic